Strategic Management to Increase Visitors of Mount Kayoe Putih, Kupang Village, Mojokerto District - Sari, Desi Ratna; Sukristyanto, Agus; Kusbandrijo, Bambang (Jurnal Manajemen Bisnis, 2024)
This study aimed to describe and analyze the strategic management to increase tourist visits to Bukit Kayoe Putih in Desa Kupang, Kabupaten Mojokerto. Using a SWOT analysis approach, this research highlighted the potential and challenges faced by this tourist attraction. The study employed a descriptive qualitative method with data collection techniques including interviews, observations, and documentation. The analysis results indicated that Bukit Kayoe Putih was well-suited to employ aggressive strategies and SO strategies to enhance tourist visits. The recommended strategies included the development of tourist attractions, conservation of eucalyptus trees, involvement of the local community in tourism development, and increased socialization with the local community. Additionally, infrastructure improvements, enhancement of tourist facilities, and better service quality were also the focus of tourism development strategies at Bukit Kayoe Putih. It was hoped that the findings of this study would contribute positively to increasing tourist visits and improving the local community's economy in the region.